math

posted by .

Solve for x in the equation (x − 7)^2 − 4 = (x + 1)^2.

  • math -

    (x − 7)^2 − 4 = (x + 1)^2
    x^2 - 14x + 49 - 4 = x^2 + 2x + 1
    -16x = -44
    x = 44/16 = 11/4 or 2.75

  • math -

    follow up quesiton

    11/4 or 2.75

    how do u convert this without using calculator?

  • math -

    to divide by 4 in my head,
    I take half of my number and then I take another half

    (little tricks that old people still know and use)

    so half of 11 is 5.5 and half of 5.5 is 2.75
    Think of money, half of $5.50
    half of $5 is 2.50, and half of 50 cents is 25 cents
    what is 2.50 + 25 cents ?

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. calculus

    Find an equation for the surface consisting of all points P(x, y, z) equidistant from the point P(0, 1, 0) and the plane x = 3. Answer Choices: 1. y2 + z2 − 6x + 2y − 8 = 0 2. x2 + z2 + 6y − 2z − 8 = 0 3. y2 …
  2. biology

    Given the part of the molecule shown below, can the underlined atom participate in a hydrogen bond with an approriate bonding partner?
  3. Product of Roots of Sums of Products of Difference

    What is the product of all roots to the equation ++(x−1)(x−2)(x−3)+(x−2)(x−3)(x−4)(x−3)(x−4)(x−5)+(x−4)(x−5)(x−6)(x−5)(x−6)(x−7)+(x−6)(x−7)(x−8)=0?
  4. Product of Roots of Sums of Products of Difference

    What is the product of all roots to the equation ++(x−1)(x−2)(x−3)+(x−2)(x−3)(x−4)(x−3)(x−4)(x−5)+(x−4)(x−5)(x−6)(x−5)(x−6)(x−7)+(x−6)(x−7)(x−8)=0?
  5. Grade 12 Calculus

    Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
  6. calculus (gr 12)

    Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
  7. calculus (gr 12)

    Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
  8. algebra

    Below are the steps to solve an equation: Step 1: |x − 2| + 3 = 7 Step 2: |x − 2| = 7 − 3 Step 3: |x − 2| = 4 Which of the following is a correct next step to solve the equation?
  9. math

    Elimination was used to solve a system of equations. One of the intermediate steps led to the equation 9x=27 . Which of the following systems could have led to this equation?
  10. math help please?!

    Solve the system by Gauss - Jordan elimination. { 1/3 x + 3/4 y - 2/3 z = -8 x + 1/2 y + 1/3 z = 18 1/6 x = 1/8 y - z = -24 a. (−6, 8, −24) b. (−6, −8, −24) c. (0, 8, −24) d. (6,8,24) e. (6, −8, …

More Similar Questions